2020
DOI: 10.1021/acs.energyfuels.0c02357
|View full text |Cite
|
Sign up to set email alerts
|

Few Layer g-C3N4 Dispersed Quaternary Phosphonium Ionic Liquid for Highly Efficient Catalytic Oxidative Desulfurization of Fuel

Abstract: Functionalized ionic liquids (ILs) have been considered as efficient catalysts for oxidative desulfurization (ODS), but the further industrial applications are hampered by the poor separability with oil phase after reaction and large dosage. In this work, few-layered graphitic carbon nitride (g-C 3 N 4 ) with high specific surface area was prepared via thermal oxidation and employed as a carrier to construct supported ionic liquid catalyst for ODS. A functional quaternary phosphonium ionic liquid [(C 6 H 13 ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 66 publications
1
15
1
Order By: Relevance
“…Similar to what was observed earlier, the developed surface area and the structure of pores in carbon materials, leading to well-dispersed active phases, were found as a critical contribution of carbon structures [114][115][116][117][118]. Xun et al (2020) [119] also highlighted the dispersion of TiO 2 over a graphite carbon (GC) as a relevant factor for the ODS of a simulated fuel (DBT, 4-methyldibenzothiophene (4-MDBT) and 4,6-DMDBT) dissolved in n-octane, [S] 0 = 500 ppm). However, they also observed that the dispersion is related to the amount of active phase dispersed on the support.…”
Section: Other Ods Systemssupporting
confidence: 84%
See 1 more Smart Citation
“…Similar to what was observed earlier, the developed surface area and the structure of pores in carbon materials, leading to well-dispersed active phases, were found as a critical contribution of carbon structures [114][115][116][117][118]. Xun et al (2020) [119] also highlighted the dispersion of TiO 2 over a graphite carbon (GC) as a relevant factor for the ODS of a simulated fuel (DBT, 4-methyldibenzothiophene (4-MDBT) and 4,6-DMDBT) dissolved in n-octane, [S] 0 = 500 ppm). However, they also observed that the dispersion is related to the amount of active phase dispersed on the support.…”
Section: Other Ods Systemssupporting
confidence: 84%
“…One of the reasons for the high activity of the materials (conversions higher than 85% in 75 min of reaction) was attributed to the high surface area of the 3D-carbon structure, which resulted in a fast mass transfer to the active sites confined within the structure [99]. Zhu et al (2020) also have observed that the 3D structure of carbon spheres (3D-CS) is beneficial to an increased mass transfer during oxidative desulfurization [97]. Bhadra et al (2017) also highlighted a fast mass transfer resultant from mesoporosity of the catalyst as an important contributor to the high activity of a TiO 2 -C in ODS of a simulated fuel (Th, BT, DBT or 4,6-DMDBT in n-octane, [S] 0 = 1000 ppm) [92].…”
Section: L-l Biphasic Systemsmentioning
confidence: 99%
“…Xun et al prepared a new few-layered graphitic carbon nitride (g-C 3 N 4 ) supported quaternary phosphonium ionic liquid [(C 6 H 13 ) 3 PC 14 H 29 ] 3 PMo 12 O 40 (C 14 PPMo IL) and employed it as a heterogenous catalyst for the oxidative desulfurization of model oil with hydrogen peroxide under solvent-free conditions ( Xun et al, 2020 ). The results showed that the supported catalyst 5% C 14 PPMo/g-C 3 N 4 exhibited extraordinary catalytic activity in the oxidative desulfurization with 100% sulfur-removal of DBT and 94.8% removal of 4,6-DMDBT after a 180-min reaction under mild conditions ( Supplementary Figure S10 ).…”
Section: Deep Oxidative Desulfurizationmentioning
confidence: 99%
“…According to the ODS principle, sulfides can be oxidized into sulfones or sulfoxides, which will be completely removed from diesel by means of absorption or extraction. Meanwhile, the appropriate oxidant is recognized as one of the critical factors to control the cost of ODS. According to recent studies, hydrogen peroxide, oxygen (O 2 ), and ozone have been employed as oxidants for ODS. To be specific, O 2 shows a better application prospect for its low cost, abundant sources, and no byproducts after the reaction. , However, the ground state O 2 is chemically inert and should usually be activated under harsh conditions . Thus, the development of high-performance catalysts to reduce the requirement for O 2 activation refers to the core issue in this field …”
Section: Introductionmentioning
confidence: 99%